2020
DOI: 10.5398/tasj.2020.43.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Eight Indonesian Swamp-Buffalo Populations Based on Cytochrome b Gene Marker

Abstract: Genetic variation is a major concern in animal genetic resources conservation program. This study aimed to analyze genetic variation and phylogeography of eight Indonesian swamp-buffalo populations based on cytochrome b gene marker. A total of 78 DNA fragment samples originating from eight Indonesian swamp-buffalo populations were used in this study, namely Bombana Island,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Colli et al (2018) explained buffaloes from China migrate from the Philippines to South Sulawesi, causing more similarity between buffaloes in the Philippines and those in South Sulawesi. Rusdin et al (2020) found two clusters of swamp buffaloes from South East Sulawesi that were different clusters from swamp buffaloes in Banten, West Nusa Tenggara, and Aceh. Moreover, it was reported that there was a genetic closeness in swamp buffaloes from the Philippines, South Sulawesi, and Southeast Sulawesi.…”
Section: Discussionmentioning
confidence: 77%
“…Colli et al (2018) explained buffaloes from China migrate from the Philippines to South Sulawesi, causing more similarity between buffaloes in the Philippines and those in South Sulawesi. Rusdin et al (2020) found two clusters of swamp buffaloes from South East Sulawesi that were different clusters from swamp buffaloes in Banten, West Nusa Tenggara, and Aceh. Moreover, it was reported that there was a genetic closeness in swamp buffaloes from the Philippines, South Sulawesi, and Southeast Sulawesi.…”
Section: Discussionmentioning
confidence: 77%
“…The data used were base positions 70 to 747 (678 bp) of Cytochrome B gene based on GenBank reference (D82894). We used those base positions to accommodate the length of cytochrome B gene sequence of swamp buffalo from Indonesia based on the result reported by Rusdin et al (2020). Sequences data were analyzed using the DnaSP v6 program to determine the haplotypes and haplotype diversity (Rozas et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Indonesia 78 (Rusdin et al, 2020) 61 haplotypes, and the haplotype diversity was 0.7020 with 62 polymorphic sites. The smallest haplotype diversity was found in Taiwan (0.1970), and the highest was found in India (1.0000).…”
Section: Bubalus Bubalismentioning
confidence: 98%
“…The age at first calving of Kuntu buffalo (54 ± 1.7 months) was greater than the Thai buffalo (47.1 months) (Chaikhun et al 2012), Brazil Buffalo (41.67 months) (Marques et al 2020), Murrah buffalo in India (52.62 months) (Thiruvenkadan et al 2015). This difference age at first calving is influenced by differences in maintenance management and feed management (Rusdin et al 2020). Bindari et al (2013) stated that nutritional adequacy will affect changes in livestock reproduction.…”
Section: Reproductive Efficiency Of Kuntu Buffalomentioning
confidence: 99%